Los hábitos de lectura y su incidencia en el aprendizaje de los niños y niñas del sexto y séptimo grado de la Escuela de Educación Básica "Calicuchima" del cantón Quinsaloma, provincia de Los Ríos, periodo lectivo 2014-2015, Guía metodológica de lectura. - Velasco Alarcón, Idalia Mabel (2015)
This research shows the problems of the poor practice of reading habits in children of the sixth and seventh grade of the School of Basic Education "Calicuchima". One of the causes is the insufficient knowledge about the importance of the implementation of study habits from the basic educational level, a situation that causes problems in the meaningful learning, which establishes a poor quality in educational levels and the difficulties of a professional nature. The purpose is to achieve with this research work is that after checking of the hypotheses formulated a viable implementation of the proposal for this mode generate changes with regard to the practice of reading habits thereby giving a solution to the problem presented. The methodology used is based on a research field of qualitative-quantitative developed through the interview applied to the steering and the surveys that were applied to teachers, students and parents respectively, through which negative results were obtained with regard to the development of the reading habits of the institution. From the analysis it appears the need to promote a change in attitude of the manager, teachers, students and parents on problems faced by the poor practice of reading habits, being each direct beneficiary from the angle that it occupies in the educational community, as with the practice of the same dramatically improves reading comprehension, therefore the learning process of children develops in an environment more effective and efficient, thus obtaining a quality education and warmth. Key Words: reading habits, knowledge, learning, education.